Custom-Made 3D-Printed Prosthesis after Resection of a Voluminous Giant Cell Tumour Recurrence in Pelvis - Adyb-Adrian KHAL; Dragos APOSTU; Calin SCHIAU; Nona BEJINARIU; Sebastien PESENTI; Jean-Luc JOUVE (Diagnostics, 2023)
Abstract: Giant-cell tumours are benign aggressive bone lesions that can affect any part of the skeleton. In early stages, curettage is preferred, but in case of local recurrence or voluminous lesions in the periacetabular region, wide resection and reconstruction are recommended. The purpose of this article is to increase clinicians’ awareness of the importance of the follow-up of these patients and to describe a case of a voluminous recurrence of a giant-cell tumour in the pelvis. We present a 25-year-old female who underwent internal hemipelvectomy assisted by 3D cutting-guides and reconstruction with a custom-made 3D-printed pelvic prosthesis, hip arthroplasty and ilio-sacral arthrodesis. No postoperative complications occurred and, at long-term follow-up, the patient had a stable and painless hip joint, good bone-implant osteointegration, with an excellent functional outcome. In spite of all available reconstructive techniques, in well-selected patients with voluminous pelvic resections, custom-made 3D-printed implants allow patients to have a good mechanical outcome.